Faktor-faktor kelewatan penyiapan projek oleh kontraktor kelas A di Kuching, Sarawak / Siti Nur Aishah Mohd Noor … [et al.] - Mohd Noor, Siti Nur Aishah; Hasbullah, Mohd Amran (2010)
The Construction industry is one of the important sectors that contribute to Malaysia's economic growth and provides a lot of opportunities to every contractor to prosper which involved in this sector. On the other hand, contractors who do not appreciate this opportunity will only caused problems in terms of extended project duration, increase in cost and low quality workmanship. This study found out that the construction delays is the most significant problems and it is keep continuing. This is due to the fact that the contractors do not have the capacity of technical know-how, lack of experience and project management skills in the related project. The main purpose of this study is to identify the factors that contribute to constructional delay projects in Kuching, Sarawak